KARAKTERISTIK FISIKOKIMIA DESICCATED COCONUT FINE GRADE DENGAN PENAMBAHAN BHT DAN TINGKAT PENERIMAANNYA OLEH KONSUMEN - Muhammad Nur Kholis; Waqif Agusta; Wendianing Putri Luketsi; Alief Fathin Nurrochman; Mokhammad Rizqi Tobibi Herman; Tantry Eko Putri Mariastuty; Herdiarti Destika Hermansyah; Tri Yulni (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Desiccated coconut, a processed product of grated and dried coconut flesh, is characterized by its white color and distinctive taste and aroma. Standard CXS 177-1991 amendment 2022 specifies that desiccated coconut fine should have at least 80% of its mass passing through a 1.40 mm sieve and no more than 20% passing through a 0.71 mm sieve. Based on the Indonesian National Standard, desiccated coconut has a fat content of 61%, which is relatively high and thus may accelerate quality degradation if not appropriately treated. This study aims to understand the potential impact of adding Butylated Hydroxytoluene (BHT) in preventing damage to desiccated coconut and finding the optimal drying temperature formula to enhance consumer acceptance. The study examines three levels of BHT addition: 0 g, 0.1735 g, and 0.347 g per batch. The research methodology employed a Complete Randomized Design (RAL) with 2 factors, with test parameters including yield, pH, water activity (Aw), phenol content, and organoleptic assessment. The findings indicate that the best treatment is sample S3B3, involving a temperature of 80°C and adding 0.347 g/ batch of BHT. This sample has the following parameters: moisture content, pH, Aw (water activity), phenol content, lightness, and hardness (Texture Profile Analysis), which are 46.37%, 2.2515%, 6.345, 0.379, 0.342 mg/GAE g, 85.27, and 5113, respectively.